Light-enhanced VEGF121/rGel induce immunogenic cell death and increase the antitumor activity of αCTLA4 treatment - Longva, Ane Sager; Berg, Kristian; Weyergang, Anette (Frontiers in Immunology, 2023)
Background: Immune-checkpoint inhibitors (ICIs) represent a revolution in cancer therapy and are currently implemented as standard therapy within several cancer indications. Nevertheless, the treatment is only effective in a subset of patients, and immune-related adverse effects complicate the improved survival. Adjuvant treatments that can improve the efficacy of ICIs are highly warranted, not only to increase the response rate, but also to reduce the therapeutic ICI dosage. Several treatment modalities have been suggested as ICI adjuvants including vascular targeted treatments and photodynamic therapy (PDT). Photochemical internalization (PCI) is a drug delivery system, based on PDT. PCI is long known to generate an immune response in murine models and was recently shown to enhance the cellular immune response of a vaccine in a clinical study. In the present work we evaluated PCI in combination with the vascular targeting toxin VEGF121/rGel with respect to induction of immune-mediated cell death as well as in vitro ICI enhancement. Methods: DAMP signaling post VEGF121/rGel-PCI was assessed in CT26 and MC38 murine colon cancer cell lines. Hypericin-PDT, previously indicated as an highly efficient DAMP inducer (but difficult to utilize clinically), was used as a control. ATP release was detected by a bioluminescent kit while HMGB1 and HSP90 relocalization and secretion was detected by fluorescence microscopy and western blotting. VEGF121/rGel-PCI was further investigated as an αCTLA enhancer in CT26 and MC38 tumors by measurement of tumor growth delay. CD8+ Dependent efficacy was evaluated in vivo using a CD8+ antibody. Results: VEGF121/rGel-PCI was shown to induce increased DAMP signaling as compared to PDT and VEGF121/rGel alone and the magnitude was found similar to that induced by Hypericin-PDT. Furthermore, a significant CD8+ dependent enhanced αCTLA-4 treatment effect was observed when VEGF121/rGel-PCI was used as an adjuvant in both tumor models. Conclusions: VEGF121/rGel-PCI describes a novel concept for ICI enhancement which induces a rapid CD8+ dependent tumor eradication in both CT26 and MC38 tumors. The concept is based on the combination of intracellular ROS generation and vascular targeting using a plant derived toxin and will be developed towards clinical utilization.